Avalanche risk reduction and community resilience building in (Badakhshan, Afghanistan) - Lashkari, Sayed Hafiz (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2022.